Evaluation of Crude Fat, Crude Fiber, and Gross Energy Content of Palm Kernel Meal Fermented with EM-4 (Effective Microorganisms-4) at Different Fermentation Durations - Putra, Randi Eka; Surtina, Dara; Harissatria, Harissatria (Department of Agriculture, 2024)
This research aims to determine the effect of fermentation time for palm kernel meal using EM-4 (Effective Microorganism-4) on the crude fat, crude fiber, and gross energy contents. This is clear, but you might add a location like